1997
DOI: 10.1029/97gb01624
|View full text |Cite
|
Sign up to set email alerts
|

Methane oxidation and pathways of production in a Texas paddy field deduced from measurements of flux, δl3C, and δD of CH4

Abstract: Abstract. Irrigated rice paddies are one of the few methane (CH4) sources where the management of its emissions may be possible. Before that can be initiated, however, the relationship between production, oxidation, and emission of CH 4 and the processes controlling them must be better known. To that end we have made measurements of concentration and stable carbon and hydrogen isotopes of CH 4 and CO 2 in paddy fields along the Gulf Coast of Texas. Although only small differences in total CH4 flux (-46.5 2 3 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
189
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(200 citation statements)
references
References 67 publications
10
189
1
Order By: Relevance
“…Water resulting from the methane combustion also was collected and frozen into a single glass tube. The measurements of d 13 C-CH 4 and d 2 H-CH 4 were performed in 1997 at the University of California, Irvine, using a Finnigan-MAT 252 isotope ratio mass spectrometer equipped with a tube cracker inlet system (Tyler et al, 1997). The CO 2 samples intended for 13 C analysis were run directly.…”
Section: Oxidation and Mass Spectrometrymentioning
confidence: 99%
“…Water resulting from the methane combustion also was collected and frozen into a single glass tube. The measurements of d 13 C-CH 4 and d 2 H-CH 4 were performed in 1997 at the University of California, Irvine, using a Finnigan-MAT 252 isotope ratio mass spectrometer equipped with a tube cracker inlet system (Tyler et al, 1997). The CO 2 samples intended for 13 C analysis were run directly.…”
Section: Oxidation and Mass Spectrometrymentioning
confidence: 99%
“…Other studies also found more reasonable values for ƒ mc when assuming α mc = 1.07 (Conrad et al, 2002;Fey et al, 2004). It is also notable that most previous studies have reported δ ac values of acetoclastic methanogenesis in the range of -23 ‰ to -46 ‰ (Goevert and Conrad, 2009;Krzycki et al, 1987;Nakagawa et al, 2002;Sugimoto and Wada, 1993;Tyler et al, 1997). Therefore the postulated δ ac values of -23 ‰ to -34 ‰ in this study are in good agreement with the δ ac values of acetoclastic methanogenesis currently reported in the literature.…”
Section: Pathway Contribution In Coal-treated Cultures and A Conceptumentioning
confidence: 79%
“…These conditions were consistently maintained throughout the sampling period to maintain uniformity in environmental conditions. The fraction of oxidation was determined using in-situ stable isotope tracing technique (Chanton et al, 1997;Tyler et al, 1997). The method makes use of naturally occurring carbon isotope ratios ( 13 C/ 12 C) between above-and below-ground was used in this research.…”
Section: Site Characteristicsmentioning
confidence: 99%
“…In a similar way, just recently, the use of hydrogen isotopes (δD) has been used in trying to understand the biogeochemistry of individual CH 4 sources (Wahlen, 1994;Quay et al, 1999;Rice et al 2009;Tyler et al, 1997). The hydrogen isotopic composition, δD, is calculated in the same way using the D/H ratio for standard mean (0.0001558) for R standard (Gonfiantini et al, 1995).…”
mentioning
confidence: 99%
See 1 more Smart Citation